Kesiapan Institusi Lokal dalam Menghadapi Bencana Tsunami: Studi Kasus Kelurahan Air Manis dan Kelurahan Purus, Kota Padang - Khoirul Anam; Abdul Mutholib; Febry Setiyawan; Bevi Astika Andini; Sefniwati Sefniwati (Jurnal Wilayah dan Lingkungan, 2018)
Aceh Tsunami’s in 2004 has a significant impact on Indonesia disaster management. Shifting of disaster management paradigm has directed to proactive preparedness that is involving some stakeholders including local institution like villages. At any level, the preparedness for the tsunami disaster of a government institution has been studied, including local government. However, in the lower level of local government such as villages have few of studies about that. Villages are institutions that deal directly with local communities. Therefore, the description of the preparedness/readiness of local institutions is needed. This study aims to give an overview of the readiness of local institutions in the face of the tsunami disaster by cases in the Air Manis Urban Village and Purus Village. Both of urban villages are located in the coastal area of Padang City which is one of the areas with high tsunami risk. This study uses descriptive qualitative approach, by using a primary data collection through in-depth interview with the key informant and secondary data collection through documents related to disaster management in Padang City. The local institution preparedness in both areas is identified through physical and non-physical aspects related to tsunami risk reduction. The results of the study showed that physically and non-physically Purus Village has better readiness compared to Air Manis Village. However, from the non-physical aspects of TRANTIB-PB and KSB as a representation of the involvement of local institutions in disaster management, it is still necessary to improve the governance in order not to become a mere formality. These two urban villages as a tourism destination are not considered in disaster management.